Characteristics of Lateral Acceleration and Vertical Acceleration of the Position of the Vehicle on the Ferry Ro-Ro Car Deck - Alamsyah bin Muhammad Saleh; Wira Setiawan; Daeng Paroka; Nurbaya Nurbaya; Handika Sanjaya Sitanggang; Muh. Reza Fachrul Jaya (Institut Teknologi Sepuluh Nopember, 2023)
Ferry accidents in Indonesia happen not just once or twice, but more than that. This is reinforced by statistical data on shipping transportation accidents. Shifting or overturning of the vehicle to the side of the ro-ro ferry has a big hand in causing the ship to capsize, and eventually an accident occurs. This study aims to determine the characteristics of the lateral and vertical acceleration of vehicles based on their location on the car deck under the influence of side waves. The method used is strip theory with the help of Maxurf software, which adheres to the B-spiline mathematical equation. The results of the study detected that vehicle positioning on the ro-ro ferry car deck significantly affects the value of vertical acceleration and lateral acceleration due to rolling motion. This is one of the parameters that can cause a vehicle to roll over.